Generating digital drug cocktails via optical manipulation of drug-containing particles and photo-patterning of hydrogels12. Issue 10 (3rd April 2019) - Chen, Yi-Sin; Chung, Ko-Chin; Huang, Wen-Yen; Lee, Wen-Bin; Fu, Chien-Yu; Wang, Chih-Hung; Lee, Gwo-Bin
Abstract : An integrated microfluidic system combining 1) ODEP for manipulation of drug-containing particles and 2) UV "direct writing" capable of patterning hydrogels was established for automatic formulation of customized digital drug cocktails. Abstract : An integrated microfluidic system combining 1) an optically-induced-dielectrophoresis (ODEP) module for manipulation of drug-containing particles and 2) an ultraviolet (UV) "direct writing" module capable of patterning hydrogels was established herein for automatic formulation of customized digital drug cocktails. Using the ODEP module, the drug-containing particles were assembled by using moving light patterns generated from a digital projector. The hydrogel, poly(ethylene glycol) diacrylate (PEGDA), was used as the medium in the ODEP module such that the assembled drug-containing particles could be UV-cured and consequently encapsulated in "pills" of specific sizes and shapes by using the UV direct writing module. At an optimal ODEP force of 335 pN, which was achieved in a solution of 15% PEGDA in 0.2 M sucrose, it was possible to manipulate and UV-cure the drug-containing particles. Furthermore, with a digital micromirror device inside the UV direct writing module, different UV patterns could be designed and projected, allowing for the digital drug cocktails to be packaged into different shapes in <60 s. As a demonstration, emulsion droplets containing two different anti-cancer drugs were further tested to show the capability of the developed device. This represents an automatic digital drug cocktail formulating device which stands to revolutionize personalized medicine.